NEW POSSIBILITIES FOR THE TREATMENT OF CHRONIC KNEE SYNOVITIS IN SURGICAL PRACTICE - F. A. Gafurov (Scholars Digest Publishing, 2024)
This article explores new treatments for chronic knee synovitis in surgery and explores new treatments for knee synovitis. In surgical practice, new methods and programs for the treatment of chronic knee synovitis are constantly developing. It is being studied by renowned medical institutes and universities.
Keywords: diagnosis, surgical treatment, chronic synovitis, arthroscopy, manipulation, hyperemia.